Analisis Kecepatan Aliran Dan Muka Air Tanah Gambut Dengan Menggunakan Groundwater Velocimeter - Irfan, Riza; Rinaldi, Rinaldi; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The objective of this research was to do an analyze velocity of the groundwater flow and surface of the groundwater using a Groundwater Velocimeter on peatlands that has been carried out by a wetting program trough the construction of a canal block for peatland hydrological restoration. Hydrological restoration of peatland with the construction of canal blocks is a common way to rewetting peatland, which is done at Lukun Village, Tebing Tinggi Timur District, Kepulauan Meranti District. The analysis of this research was using Groundwater Velocimeter, it is used to measure velocity and direction of the groundwater flow carried out on monitoring well built around canal blocks.The method that is used of this research was Image J and Visual. The result showed that the comparison of velocity of the groundwater flow using Image J method has a little different from the Visual method.The highest velocity of the groundwater occured in deep well 2 transect 1, based on the Image J method which obtained a velocity of 0.432 m/day, and for the Visual method which obtained a velocity 0.587 m/day. Key words: Canal Blocks, Groundwater Velocimeter, Image J, Peatlands